Viewing Strategies in Children With Visual Impairment and Children With Normal Vision: A Systematic Scoping Review - Fonteyn-Vinke, Anke; Huurneman, Bianca; Boonstra, Frouke N. (Frontiers in Psychology, 2022)
Viewing strategies are strategies used to support visual information processing. These strategies may differ between children with cerebral visual impairment (CVI), children with ocular visual impairment, and children with normal vision since visual impairment might have an impact on viewing behavior. In current visual rehabilitation practice a variety of strategies is used without consideration of the differences in etiology of the visual impairment or in the spontaneous viewing strategies used. This systematic scoping review focuses on viewing strategies used during near school-based tasks like reading and on possible interventions aimed at viewing strategies. The goal is threefold: (1) creating a clear concept of viewing strategies, (2) mapping differences in viewing strategies between children with ocular visual impairment, children with CVI and children with normal vision, and (3) identifying interventions that can improve visual processing by targeting viewing strategies. Four databases were used to conduct the literature search: PubMed, Embase, PsycINFO and Cochrane. 799 articles were screened by two independent reviewers using PRISMA reporting guidelines of which 30 were included for qualitative analysis. Only five studies explicitly mentioned strategies used during visual processing, namely gaze strategies, reading strategies and search strategies. We define a viewing strategy as a conscious and systematic way of viewing during task performance. The results of this review are integrated with different attention network systems, which provide direction on how to design future interventions targeting the use of viewing strategies to improve different aspects of visual processing.